Mensch und Computer 2015 - Usability Professionals Humans and Computers 2015 Usability Professional Workshop - Endmann, Anja (De Gruyter, 2015)
Usability Professionals Workshop deals with the practical applications of human-machine interaction research. It is organized by the German ACM specialty section of the UPA (Usability Professionals Association). The volume presents the latest research findings through case studies and practice reports along with in-depth discussions.